ChemInform Abstract: Synthesis of Indolizines and Heterocyclic Chalcones Catalyzed by Supported Copper Nanoparticles. Issue 38 (30th August 2013) - Albaladejo, Maria Jose; Alonso, Francisco; Yus, Miguel
Abstract The authors describe the synthesis of different substituted indolizine derivatives via a multicomponent reaction and the synthesis of heterocyclic chalcones with the same starting materials but without addition of a solvent.